Actualizing Indigenous Knowledge in tribal wildlife management: basic preconditions - Tony Ciocco; Stefan Tangen; Chad Smith (Wildlife Society Bulletin, 2023)
Abstract Indigenous Knowledge (IK) is increasingly involved in the contemporary management of natural resources. Tribal wildlife management programs in the United States may be uniquely positioned to effectively and ethically integrate their IK. While a narrow focus on the body of IK and a particular management activity may suffice for project‐level integration efforts, herein we consider how IK integration at the programmatic level may be best supported. We propose a holistic conceptual framework of preconditions including sovereignty, the North American Model management, funding, cultural resources, stakeholder support, and programmatic leadership. We assess the current status and common challenges with each precondition and illustrate their potential roles for a more lasting and pervasive integration of IK into tribal wildlife management programs.